Liquid crystal precursor mucoadhesive system as a strategy to improve the prophylactic action of Syngonanthus nitens (Bong.) Ruhland against infection by Candida krusei - Santos Ramos, Matheus Aparecido dos [UNESP]; Calixto, Giovana; Toledo, Luciani Gaspar de [UNESP]; Bonifacio, Bruna Vidal; Santos, Lourdes Campaner dos [UNESP]; Gottardo de Almeida, Margarete Teresa; Chorilli, Marlus [UNESP]; Bauab, Tais Maria [UNESP] (Dove Medical Press Ltd, 2015)
Vaginal infections caused by Candida krusei are a problem of extreme complexity due to the intrinsic resistance to azole drugs. The species Syngonanthus nitens (Bong.) Ruhland is a plant of the Eriocaulaceae family that has demonstrated promising antifungal activity. In phyto-formulation research, liquid crystal precursor mucoadhesive systems (LCPM) stand out as drug delivery systems for vaginal administration because they increase the activity and overcome the problems associated with plant-based medicines. Therefore, the objective of this study was to evaluate the potential of the methanolic extract of scapes of S. nitens (S. nitens extract [SNE]) and an SNE-loaded LCPM against C. krusei as prophylaxis for vulvovaginal candidiasis. LCPM formulation developed consisted of oleic acid as the oil phase (50% w/w), polyoxypropylene (5) polyoxyethylene (20) cetyl alcohol (40% w/w) as the surfactant and a polymeric dispersion containing 2.5% Carbopol (R) 974P and 2.5% polycarbophil (10% w/w) as the aqueous phase. LCPM formulation developed was characterized using polarized light microscopy, rheological analysis, and in vitro mucoadhesive studies. Different strains of C. krusei, including one standard strain (American Type Culture Collection 6258) and three clinically isolated strains from the vaginal region (CKV1, 2, and 3), were used to determine the minimum inhibitory concentration, inhibition of biofilms, and time kill. The in vivo prophylaxis assay was performed using the standard strain (American Type Culture Collection 6258). The analyses of F by polarized light microscopy and rheology showed isotropy; however, the addition of 100% artificial vaginal mucus (F100) made it more viscous and anisotropic. Moreover, the mucoadhesive strength was modified, which makes F an excellent formulation for vaginal applications. SNE was active against all strains studied, with minimum inhibitory concentration values ranging from 125 to 62.5 mu g/mL; after incorporating SNE into F (FE), these values decreased to 62.5 to 31.2 mu g/mL, demonstrating that incorporation into the formulation potentiated the action of SNE. Additionally, the time kill assays showed that both forms of SNE were capable of controlling growth, thereby suggesting a possible fungistatic mechanism. Unloaded SNE was not active against C. krusei biofilms, but FE was active against a clinical strain (CKV2). In vivo analysis showed that FE was able to prevent the development of infection following 10 days of administration. We concluded that the formulation developed in this study was an important vehicle for the delivery of SNE based on the improved antifungal activity in all in vitro and in vivo analyses. Furthermore, the extract incorporated into the system may serve as an important prophylactic agent against vaginal infections caused by C. krusei.
Keywords: precursor system of mucoadhesive liquid crystal; nanostructured system; prophylaxis; Candida krusei